2018
DOI: 10.3390/agronomy8070128
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Field Crops Sensitivity to Heat Stress: Mechanisms, Approaches, and Future Prospects

Abstract: The astonishing increase in temperature presents an alarming threat to crop production worldwide. As evident by huge yield decline in various crops, the escalating drastic impacts of heat stress (HS) are putting global food production as well as nutritional security at high risk. HS is a major abiotic stress that influences plant morphology, physiology, reproduction, and productivity worldwide. The physiological and molecular responses to HS are dynamic research areas, and molecular techniques are being adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 272 publications
(293 reference statements)
0
49
0
1
Order By: Relevance
“…Drought and heat stress are two major environmental stresses that threaten the sustainable crop production worldwide (Nadeem et al, 2018). It has been reported that extreme heat stress weathers have caused a very large amount of grain yield loss in many regions of the world (Ciais et al, 2005;He et al, 2018;Smith and Katz, 2013;Yang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Drought and heat stress are two major environmental stresses that threaten the sustainable crop production worldwide (Nadeem et al, 2018). It has been reported that extreme heat stress weathers have caused a very large amount of grain yield loss in many regions of the world (Ciais et al, 2005;He et al, 2018;Smith and Katz, 2013;Yang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A number of papers consider the effect of heat and drought stress on crops. Nadeem and coworkers review the diverse effects of heat stress on crop yield [14]. They report that heat stress is especially deleterious to certain developmental stages, including the generation and function of reproductive organs.…”
Section: Abiotic Stress Responses and The Usage Of Rna-seq Methodologymentioning
confidence: 99%
“…In the field, abiotic stresses can occur in isolation or together to impact phenotypical, physiological, biochemical, and/or molecular aspects of crop development. Heat stress, can have significant implications on important plant activities, such as seed germination, plant development, photosynthesis, and reproduction, which leads to reductions in plant growth and crop yield (Rieu et al, 2017;Nadeem et al, 2018). The most recent IPCC report predicts a global increase of more than 4°C until the end of the century and a more frequent occurrence of severe heat waves (Change, 2014).…”
Section: Introductionmentioning
confidence: 99%